Algoritmo y noticia de datos como el futuro del periodismo transmediaimagético - Renó, Denis [UNESP]; Renó, Luciana (Forum XXI, 2017)
Currently, studies in communication and especially journalism are necessary, even a challenge. This is justified by the dynamism of contemporary media ecosystem, which corresponds to the media, emerging technologies and societies, increasingly participant in communication processes. In fact, these transformations have changed not only the processes but also the compositions of the professional groups, which work in the construction of contemporary news, now multi-language and designed to devices previously adopted, such as mobile phones and tablets. Like the data journalism, which considers the phenomenon of big data and information available in the cloud, despite to not stand out so important when disguised between contents. The crescent participation of professionals in the sciences and engineering is explained to work with these files and binary scenarios, leading to think about selection, cleaning, understanding and build public space from digital concepts of multiplatform. In this study, it was adopted some methodological procedures which include bibliographies research, as fundamental research to understand the process of evolution and practice of journalism comprising the fundamental data to develop the proposal initially raised. With the conclusion of this study, we can understand the Transmedia Journalism as perfect language to develop content based in Big Data, Algorithms for a current data journalism. This is the proposal offered in the paper.
Algorithm and data news as the future of imagetic transmedia journalism
Keywords: Data Journalism; Media Ecology; Photography; Transmedia Journalism